Playgrounds: Safe designs and infrastructures for our children… an urgent matter in Costa Rica - Morera-Castro, María (2007)
The purpose of this article is to offer the design and infrastructure parameters necessary to have safe playgrounds since they represent a unique opportunity to foster an integral development, particularly in children.  In these public places, children learn to resolve conflicts to continue playing, having fun, and developing.  These recreational areas then become learning places that foster the formation process and provide great social, emotional, physical, cognitive, intellectual, and spiritual benefits.  However, such benefits are diminished by the lack of interest of the communities and the adult population to optimize playground conditions and by unscrupulous developers, who design playgrounds in inappropriate places putting the population at risk.  Therefore, the following must be taken seriously into consideration before, during, and after the construction of a playground: design, construction, materials, equipment, components and the procedures to meet the necessary safety requirements and the objective for which they were created, that being an area designed, equipped, and located exclusively for playing that facilitates the integral development of the population.  Consequently, it is urgent for Costa Rica to enact clear regulations that guarantee the construction, design, and use of playgrounds that do not put the population’s health at risk, prevent accidents, and guarantee the inalienable rights of each Costa Rican.